Self-reported medication adherence in differentiated thyroid cancer survivors: Role of illness perception and medication beliefs - Basım, ?Pelin; Arğun, Derya; Özdenkaya, Yaşar (Wiley, 2021)
Background To investigate medication adherence (MA) to Levothyroxine in differentiated thyroid cancer survivors and analyze the related factors for nonadherence. Methods The Medication Adherence Report Scale (MARS), Hospital Anxiety and Depression Scale (HAD), Brief Illness Perception Questionnaire (B-IPQ), and Beliefs about Medicines Questionnaire (BMQ) were used to assess MA. Results Nonadherence was reported in 77 of 197 patients (39.1%). Socioeconomic status and education levels were found to be significantly related to MA. The HAD scores, all items of B-IPQ, and BMQ were associated with MA and showed a correlation with the MARS scores. The primary predictors of MA were greater confidence in treatment modality (odds ratio [OR]: 0.48, 95% confidence interval (CI): 0.37-0.63) and greater belief that the medication had minimal risk of harm (OR: 3.35, 95% CI: 1.50-7.49). Conclusions Special attention should be paid to educational programs for differentiated thyroid carcinoma patients concerning the effectiveness and low risk of harm of medication in order to improve MA.
Keywords: Differentiated Thyroid Cancer; Levothyroxine; Medication Adherence; Medication Beliefs